Kemampuan Mahasiswa dalam Memecahkan Masalah Trigonometri Ditinjau dari Gender - Suesthi Rahayuningsih (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2020)
This study aimed to include: 1) Describe the ability of male students to solve trigonometric problems, and 2) Describe the abilities of female students in solving trigonometric problems. The subjects used in this study were taken from students of the Mathematics Education Study Program, namely one female student and one male student. This research was a qualitative description research. Data collection was done by task-based interviews. The interview revealed the ability of students to solve trigonometric problems based on Polya's steps, namely understanding the problem, making plans, implementing plans and checking again. The data in this study were the results of interviews and tests of mathematical problems. The results showed significant differences between the two subjects. In the stage of understanding the problem, the stage of understanding the problem of male subjects uses more symbols in writing things that were known than female subjects. At the stage of compiling a completion plan, female subjects were more consistent in using formulas than male subjects. At the stage of carrying out the settlement plan, male subjects were better at using principles and writing symbols than women. At the stage of re-checking the settlement, female subjects were more systematic than male subjects.